Fault Detection of Mechanical Equipment Failure Detection Using Intelligent Data Analysis - Maksim Andreevich Kovito (Ikatan Ahli Informatika Indonesia, 2022)
Poor maintenance of machinery in manufacturing plants has always been an important link in the production process. In addition to computer technology, artificial intelligence technologies and various intelligent sensors are widely used in manufacturing industries. The amount of data generated by production machines and equipment at all stages of the production process is also growing rapidly, and it is particularly important to analyze the data generated by these devices in order to detect and even predict malfunctions. Intelligent data mining provides advanced data analysis techniques for this purpose. This article introduces the basic concepts of data mining, its processes, the main data mining technologies, and provides recommendations for applying data mining to detect failures in devices.